Morphological study of four sections of genus Dendrobium Sw. (Orchidaceae) in Peninsular Malaysia - Moudi, Maryam; Go, Rusea (Pakistan Botanical Society, 2017)
A morphological study of the four sections (Aporum, Crumenata, Strongyle, and Bolbidium) of the genus Dendrobium (family Orchidaceae) was conducted by using 18 morphological characters. One of the three largest Orchid genera in Orchidaceae is genus Dendrobium. This genus is distributed from South- East Asia, west to the Himalayas, east to Japan, and south to the Pacific Islands, New Zealand and Australia. Dendrobiums are one of the most popular orchids for their medicinal and commercial values. This plant occurs in the tropical regions with high annual rainfall and without a significant dry season for growth. In this study, 17 fresh samples of Dendrobium species were collected and identified upto the species level. The statistical analysis indicated he occurrence of two groups. The first group had four sections (Aporum, Crumenata, Strongyle and Bolbidium) and the other group had three sections (Dendrobium, Callista and Latouria), which were closely related. The morphological analysis showed that the four sections formed a monophyletic group compared to three other sections Dendrobium, Callista and Lautoria. The results demonstrated that sections Aporum, Crumenata, and Strongyle were close to one another and were grouped into one clade. Although section Bolbidium was close to them but it formed a different clade by itself. The three other sections included in the analysis formed a separate clade from these four sections .In all, according to the cluster and cladistics analysis, these four sections (Aporum, Crumenata, Strongyle and Bolbidium) can be put in the separate clade compared to the other sections of genus Dendrobium an can be named Aporum based on ICBN rules.